1990
DOI: 10.1111/j.1699-0463.1990.tb05029.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the liver

Abstract: The radiologic and histologic features of an inflammatory pseudotumor of the liver in a 62‐year‐old man are presented. The lesion was coincidentally discovered during clinical work‐up of an acute pancreatitis caused by choledocholithiasis. Malignancy was suspected in the light of the radiologic presentation. To our knowledge, only 23 cases of inflammatory pseudotumor of the liver have appeared in the international literature. Its etiology remains unknown, although reactive‐inflammatory or infectious mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In our case, the hepatic IPT was initially circular with low attenuation, consistent with the major histological features of lymphoplasmacytic proliferation. We subsequently observed a spontaneous regression of the hepatic ITP, similar to several reported cases [3,6]. Lopez et al hypothesized that a hepatic ITP is an exuberant hepatic reaction to bile stasis because the reestablishment of bile flow seems to be a definitive event in its regression.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our case, the hepatic IPT was initially circular with low attenuation, consistent with the major histological features of lymphoplasmacytic proliferation. We subsequently observed a spontaneous regression of the hepatic ITP, similar to several reported cases [3,6]. Lopez et al hypothesized that a hepatic ITP is an exuberant hepatic reaction to bile stasis because the reestablishment of bile flow seems to be a definitive event in its regression.…”
Section: Discussionsupporting
confidence: 86%
“…Lopez et al hypothesized that a hepatic ITP is an exuberant hepatic reaction to bile stasis because the reestablishment of bile flow seems to be a definitive event in its regression. Although the etiology of an IPT remains unclear, an important mechanism is that it can develop as a complication of cholangitis [2][3][4][5][6]. In the present case, the recurrent IPT appeared as an unusual tumor formation along the intrahepatic bile ducts, probably due to the development of intrahepatic cholangitis with biliary stasis or regurgitation after a choledochojejunostomy.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Although the tumor is benign, its etiology remains unknown. Infection and biliary obstruction could be contributory causes to this lesion [9,13,19] . Studies from Japan reported several cases of the disease in association with autoimmune diseases of the pancreatobiliary system such as autoimmune sclerosing pancreatitis and primary sclerosing cholangitis [17,20] .…”
Section: Discussion ▼mentioning
confidence: 99%